ANNEALING TEMPERATURES’ EFFECTS ON MICROSTRUCTURE AND OPTICAL PROPERTIES OF Ba0.95Sr0.05TiO3 FILMS - Yofentina Iriani; Fahru Nurosyid; Ratna Mayasari; Dianisa Khoirum Sandi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
ANNEALING TEMPERATURES’ EFFECTS ON MICROSTRUCTURE AND OPTICAL PROPERTIES OF Ba0.95Sr0.05TiO3 FILMS. Ferroelectric materials, one of which is Barium Strontium Titanate (BST), can be applied for photovoltaic. Ferroelectric films function as the P-type semiconductor in the P-N junction. BST (Ba0.95Sr0.05TiO3) films have been deposited on Pt/Si (111) and quartz substrates via the CSD method prepared by spin coater. The films were annealed at various temperatures of 800 °C, 900 °C, and 1000 °C to observe the annealing temperatures' effects on the microstructure and optical properties of the BST films. From the XRD results, the intensity of diffraction peaks gets higher along with the higher annealing temperature. It thus causes the level of crystallization and the crystal size of the Ba0.95Sr0.05TiO3 films to increase. The morphology results reveal that the grains size of the Ba0.95Sr0.05TiO3 films is getting larger with the higher annealing temperature. The optical properties examined in the Ba0.95Sr0.05TiO3 films include absorbance and bandgap energy values. Values of bandgap energy show a decrease with increasing sintering temperature. The smallest bandgap energy of the Ba0.95Sr0.05TiO3 film is achieved at 1000 °C of 3.20 eV. BST films were annealed at temperature 1000 °C attained from this study can be considered as candidate for a photovoltaic ferroelectric material.